Octanoic acid promotes clearance of antibiotic-tolerant cells and eradicates biofilms of Staphylococcus aureus isolated from recurrent bovine mastitis - Wen-Chun Lin; Kai-Chen Hsu; Ming-Feng You; Kuo-Hua Lee; Chau-Hwa Chi; Jyh-Yih Chen (Biofilm, 2023)
Antibiotic therapy is the primary treatment for bovine mastitis, but the drawbacks of this strategy include poor cure rate and economic losses from the need to discard milk with antibiotic residues. Unfortunately, few other treatment options are currently available for mastitis. Failure of antibiotic treatments is often attributed to formation of bacterial biofilms and abscesses in the mammary gland tissue, which lead to chronic infections that are difficult to eradicate and drive recurrent disease. A major mastitis-causing pathogen (MCP) associated with biofilms in bovine mastitis is Staphylococcus aureus. In this study, we demonstrate that octanoic acid has broad-spectrum microbicidal activity against MCPs and effectively inhibits S. aureus biofilm formation in milk (>50% inhibition at 3.13 mM). Octanoic acid effectively clears biofilms (95% eradication at 1X minimum bactericidal concentration, MBC) and infrequently induces S. aureus small colony variants (SCVs) that may cause recurrent mastitis. Additionally, octanoic acid rapidly kills persistent biofilm cells and cells with antibiotic tolerance (within 4 h). In contrast, antibiotics treated at >100X MBC cannot eradicate biofilms but do induce SCVs and antibiotic-tolerant cells. These effects may accelerate the transition from biofilm to chronic infection. Thus, octanoic acid exhibits bactericidal action against S. aureus biofilms, and it is less likely than antibiotic therapy to induce persistent cells and pathogen tolerance. Moreover, octanoic acid acts additively with antibiotics against S. aureus, and it attenuates tetracycline-induced virulence factor gene expression in S. aureus cells. According to these data, octanoic acid may prevent the pathological progression of bovine mastitis and offer a new strategy for treating the condition.